Swedish Foreign Policy, 1809-2019 - Julia Forsberg (The Thinker)
Reading Graeme D. Eddie’s book – Swedish Foreign Policy, 1809–2019: A Comprehensive Modern History – is a remarkable history lesson. And don’t get me wrong, it is in no way like the boring, never-ending, tedious history lectures held by a dull teacher who talks way too slowly; it’s something else. While being a historical review, the book is a real page turner! It’s detailed, it’s informative, yet gripping. In the current reality, where Sweden is joining the North Atlantic Treaty Organization (NATO) and where the Sweden Democrats, a populist right-wing party, are now the second largest party, it is relevant to look back in order to understand the present. Reading this book is an excellent start.